1991
DOI: 10.1590/s0034-89101991000200011
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de astrovírus humanos na cidade de São Paulo, Brasil

Abstract: Foram detectados astrovírus humanos durante estudo longitudinal de 13 meses sobre a incidência de vírus diarréicos em 146 crianças menores de 2 anos de idade, hospitalizadas em clínica pediátrica de um hospital universitário, na cidade de São Paulo, SP, Brasil. Das 67 crianças internadas com diarréia aguda, 3% foram positivas para astrovírus, por ocasião de sua admissão, pelo Ensaio Imunoenzimático Monoclonal Amplificado (ASTROVIRUS BIOTIN-AVIDIN ELISA, CDC, USA). As 79 crianças sem diarréia, admitidas durante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 3 publications
1
3
0
1
Order By: Relevance
“…Our data corroborate the findings reported by Mendes (1997) during a serosurvey study conducted in Belém, Brazil, when it was demonstrated that HAstrV seropositivity rates increased from 13.9%, at 6 months of age to 64.9% in children up to 2 years old, suggesting that HAstrV infection is more frequent than the previously reported (Nozawa et al 1985, Leite et al 1991, Stewien et al 1991, Timenetsky et al 1993, Tanaka et al 1994.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our data corroborate the findings reported by Mendes (1997) during a serosurvey study conducted in Belém, Brazil, when it was demonstrated that HAstrV seropositivity rates increased from 13.9%, at 6 months of age to 64.9% in children up to 2 years old, suggesting that HAstrV infection is more frequent than the previously reported (Nozawa et al 1985, Leite et al 1991, Stewien et al 1991, Timenetsky et al 1993, Tanaka et al 1994.…”
Section: Discussionsupporting
confidence: 92%
“…The symptoms associated with diarrhea persisted for three to six days. detection could explain the low rate of detection and the lack of information about the circulating HAstrV types (Nozawa et al 1985, Leite et al 1991, Stewien et al 1991, Timenetsky et al 1993, Tanaka et al 1994. However, in a study carried out among inpatient children, we detected different serotypes of HAstrV circulating at higher rate (15%) (Silva et al unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, there are few studies about the occurrence of these viruses which show prevalence rates ranging between 3 and 56% (Stewien et al 1991, Tanaka et al 1994, Silva et al 2001, Gabbay et al 2006. Considering the Central West region of the country, only one study was carried out which showed astrovirus detection rate of 2.8% (Cardoso et al 2002).…”
mentioning
confidence: 99%
“…Entre os vírus acima citados , alguns já foram detectados em nosso meio, a partir de casos de gastroenterite. Stewien et al, (1991) evidenciaram astrovírus realizando análises com imunomicroscopia eletrônica em fase sólida (SPIEM) com suspensões fecais de crianças lactentes com diarréia, hospitalizadas na cidade de São Paulo. Astrovírus foram detectados por microscopia eletrônica e confirmados por SPIEM nas fezes de uma criança com gastroenterite , em um surto ocorrido numa mesma família, no estado de São Paulo (Tanaka et al, 1994).…”
Section: Dados Históricosunclassified